Geological interpretation of the folk legends of the Santa Lucía peak/volcano west of the Ujarrás Valley, Paraíso, Cartago, Costa Rica, and its relationship with particular elements of its physiographic context: no - Sanabria-Coto, Iván Josué (2021)
The study area of the present investigation is located 4 km southeast of the city of Paraíso, de Cartago and west of the Ujarrás Valley, the objective was to propose a geological interpretation of the folk legends collected in Prado’s book Nuestra Señora de la Virgen de Ujarrás (1921) (translated as Our Lady of the Virgin of Ujarrás) linked to the alleged existence and activity of a peak or volcano known as Santa Lucía or El Picacho. For this endeavor, it was initially necessary to perform a compilation of historical information as well as field collection of particular evidence of the associated physiographic context; next, field collected data and geospatial inputs were analyzed and integrated for the preparation of results. From the identified tectonism in the immediate geographical area and its possible natural interactions, it is feasible to support an assertive geological interpretation, of non-volcanic nature, regarding the origin of the folk legends in connection to the alleged existence of the Santa Lucía peak/volcano in the Ujarrás Valley.